Analysis of The Impact of Competence on Performance: An Investigative In Educational Institutions - Iskamto, Dedi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study aims to determine the impact of competence on performance: an investigative study in educational institutions. This research is important to do to find out the variables to improve the quality of education by looking at the teacher's performance. This research is a quantitative research with data processing and hypothesis testing using SPSS version 25. The entire population of teachers from the two schools that became the object of the study was sampled. The influence of the competence variable on the performance variable is 57.8% while the remaining 42.2% is influenced by other variables that are ignored or not examined in this study.